Introduction: Current Directions in Australian Anthropologies of the Environment - Mulcock, Jane (The Australian journal of anthropology, 2005)
Environmental anthropology is an expanding field in Australia. Extensive research on Aboriginal relationships to land and natural resources has provided the foundation for growing anthropological interest in the interactions of other Australians with the biophysical environments they inhabit. Australian-based anthropologists also continue to contribute to research on environmental beliefs and practices in other parts of the world. This paper provides a brief overview of previously explored themes in this field as a precursor to introducing new research and proposing additional areas of research. It is suggested that these could be usefully developed to enhance anthropological contributions to debates about environmental change in Australia and surrounding regions. We argue that there are roles for anthropologists as `cultural translators' in cross-disciplinary engagements with environmental scientists and natural resource managers; as cultural theorists skilled at documenting and interpreting changing environmental attitudes; and as environmental advocates pursuing the knowledge needed to create more ecologically sustainable human communities. We also suggest that Australian anthropologies of the environment can make valuable theoretical and ethnographic contributions to this important international field of study.